Hereditary spastic paraplegia due to a novel mutation of the REEP1 gene: Case report and literature review. Issue 3 (January 2017) - Richard, Sébastien; Lavie, Julie; Banneau, Guillaume; Voirand, Nathalie; Lavandier, Karine; Debouverie, Marc
Abstract: Rationale: Hereditary spastic paraplegia (HSP) is a heterogeneous group of diseases little known in clinical practice due to its low prevalence, slow progression, and difficult diagnosis. This results in an underestimation of HSP leading to belated diagnosis and management. In depth diagnosis is based on clinical presentation and identification of genomic mutations. We describe the clinical presentation and pathogeny of HSP through a report of a case due to a novel mutation of the REEP1 gene ( SPG31 ). Patient concerns: A 64-year-old woman presented gait disturbances due to spasticity of the lower limbs progressing since her third decade. Previous investigations failed to find any cause. Interventions: DNA analysis was performed to search for HSP causing mutations. Diagnoses: A novel heterozygote mutation (c.595 + 1G>A) of the REEP1 gene, within the splice site of intron 6, was discovered. This nucleotide change causes exon 6 skipping leading to frame shift and a truncated transcript identified by complementary DNA sequencing of reverse transcription polymerase chain reaction products. Outcomes: REEP1 is a known protein predominantly located in the upper motor neurons. Mutation of REEP1 primary affects the longest axons explaining predominance of pyramidal syndrome on lower limbs. Lessons: Slow progressive pyramidal syndrome of the lower limbs should elicit a diagnosis of HSP. We describe a novel mutation of the REEP1 gene causing HSP. Pathogeny is based on resulting abnormal REEP1 protein which is involved in the development of longest axons constituting the corticospinal tracts. Abstract : Supplemental Digital Content is available in the text